Digitalization of colourimetric sensor arrays for volatile fatty acid detection in anaerobic digestion - Lamb, Jacob J. (MethodsX, 2019)
During the process of converting the organic matter into methane, many volatile fatty acids (VFAs) are produced during acidogenesis and acetogenesis phases of the process. The main VFAs of interest are acetic acid, butyric acid and propionic acid. Although the production of these VFAs are essential for the production of methane, they also play an inhibitory role for many of the organisms involved in the production of biogas. As a consequence, the levels of VFAs produced in an anaerobic digester must be monitored. Current methodologies for VFA monitoring are either unspecific, or costly. Therefore, the development of a sensor method that is specific to the different VFAs, while maintaining a low cost, will facilitate the lowering of biogas production, as well as avoiding the costly biological collapse of the whole biogas production process. Here, an array of coloured dyes (colourimetric array) has been assessed for their ability to detect low concentrations of VFAs within the digestate during biogas production. This methodology lays the foundation for the development of a sensor system for use in biogas plants and could also be expanded to detect many other parameters within the biogas production process. • Easy to establish. • Low user input. • Accurate measurement.